Estimation of the Available Bandwidth of the Cellular Network Connection with Android API - Maxim Gering; Nikolai Mareev; Eduard Siemens (Proceedings of the International Conference on Applied Innovations in IT, 2022)
The speed at which mobile and wireless networks are currently developed continues to be astounding. The rate of data reception and transmission over a wireless network becomes a major factor for consumers and mobile phone service providers, as service providers compete with each other for leading positions in the quality of mobile communications provided. This paper describes the problem of available bandwidth estimation of the LTE network in dense urban environments under the TCP BBR Congestion Control protocol. For this, the open-source HTWK Signal Harvester app from the Leipzig University of Applied Sciences has been modified to estimate the available bandwidth of a connected 4G LTE network. The test results presented in the article show that the available bandwidth gathered from Android 11 API metrics are close to the results obtained by iPerf3, a stand alone utility for active measuring of maximum achievable bandwidth on IP networks, widely used in PC and server computers.